Design of CRC circuit for 5G system using VHDL - Adham Hadi Saleh; Hayder Khaleel AL-Qaysi; Khalid Awaad Humood; Tahreer Mahmood (Bulletin of Electrical Engineering and Informatics, 2023)
In this document, we focus on how to design cyclic redundancy check (CRC) circuits with different 5G polynomial divisor using very high-speed integrated circuit (VHSIC) hardware description language (VHDL) to integrate in field-programmable gate array (FPGA) suitable kit using a suitable design code. The different between designed circuits came from the different of data size according to polynomials requirements conditions since there are huge data size in 5G system that required divide it with suitable method and then implemented the required circuit. CRC code as a polar code and short low density parity check (LDPC) is proposed in 5G new radio (NR) systems, CRC properties to divided data and CRC cod make it particularly very useful for codes with higher data rate and longer lengths, and for codes with low data rates and small length as an error detection method. The CRC encoder circuit (transmitter side) and CRC decoder circuit (receiver side) with different polynomial and data size have been designed using VHDL. Xilinx ISE 14.3 simulator, where the test bench simulation results give the expected simulator results of proposed decoding circuit scheme so to integrated using ZYNQ FPGA kit.